Dietary protease improves growth rate and protein digestibility of growing-finishing pigs - Jeong Jae Lee (Journal of Animal Science and Technology, 2020)
This research was performed to investigate the hypothesis that dietary mono-component protease (PRO) might improve growth performance, nutrient digestibility, and carcass characteristics of growing-finishing pigs. A total of eighty-four pigs [Duroc × (Landrace × Yorkshire), 25.3 ± 2.16 kg initial body weight] were randomly assigned to three dietary treatments (7 replicates/treatment; 2 barrows and 2 gilts/replicate) in a randomized complete block design (block = sex). The dietary treatments were prepared as follows; (1) a positive control (PC) as a typical growing-finishing diet based on corn and soybean meal, (2) PC added with 0.015% of PRO (PCPRO), and (3) a negative control (NC) added with 0.015% of PRO (NCPRO). The NC had a lower concentration of crude protein (CP) compared with PC. The PRO was a commercial product that contained 75,000 protease units/g and derived from Nocardiopsis prasina produced in Bacillus licheniformis. Dietary treatments were offered to pigs during growing and finishing periods. Measurements were growth performance, apparent total tract digestibility (ATTD) of nutrients, and carcass characteristics. The PCPRO and/or NCPRO increased average daily gain (ADG) and gain to feed ratio (G:F) during growing (p < 0.10), finishing (p < 0.05), and growing-finishing periods (p < 0.10) compared with PC. Furthermore, pigs fed PCPRO and NCPRO had higher (p < 0.05) ATTD of CP and energy during growing and/or finishing periods than those fed PC. In conclusion, the supplementation of PRO in diets improved growth performance and protein digestibility of growing-finishing pigs.